Gastric emptying of solutions containing the natural sweetener erythritol and effects on gut hormone secretion in humans: A pilot dose‐ranging study. Issue 6 (26th February 2021) - Wölnerhanssen, Bettina K.; Drewe, Jürgen; Verbeure, Wout; le Roux, Carel W.; Dellatorre‐Teixeira, Ludmilla; Rehfeld, Jens F.; Holst, Jens J.; Hartmann, Bolette; Tack, Jan; Peterli, Ralph; Beglinger, Christoph; Meyer‐Gerspach, Anne C.
Abstract: Aim: To determine whether a dose‐dependent effect in the stimulation of gut hormone release (plasma cholecystokinin [CCK], active glucagon‐like peptide‐1 [aGLP‐1] and peptide tyrosine tyrosine [PYY]) is found for the natural sweetener erythritol. Materials and Methods: Twelve healthy, lean volunteers received solutions with 10, 25 or 50 g erythritol, or tap water enriched with 13 C‐sodium acetate on four study days via a nasogastric tube in this randomized (active treatments), placebo‐controlled, double‐blind, cross‐over trial. Blood samples and breath samples ( 13 C‐sodium acetate method for measurement of gastric emptying [GE]) were taken at regular intervals, and sensations of appetite and gastrointestinal symptoms were rated. Results: We found (a) a dose‐dependent stimulation of CCK, aGLP‐1 and PYY, and slowing of GE, (b) no effect on blood glucose, insulin, motilin, glucagon or glucose‐dependent insulinotropic polypeptide, (c) no effect on blood lipids and uric acid, and (d) no abdominal pain, nausea or vomiting. Conclusions: Solutions with 10 and 50 g of erythritol stimulated gut hormone release. Emptying of erythritol‐containing solutions from the stomach was slower compared with placebo. There was no effect on plasma glucose, insulin, glucagon, blood lipids or uric acid. All doses were well tolerated.